Management of patients with type 2 diabetes in cardiovascular rehabilitation. (December 2019) - Hansen, Dominique; Kraenkel, Nicolle; Kemps, Hareld; Wilhelm, Matthias; Abreu, Ana; Pfeiffer, Andreas FH; Jordão, Alda; Cornelissen, Veronique; Völler, Heinz
The clinical benefits of rehabilitation in cardiovascular disease are well established. Among cardiovascular disease patients, however, patients with type 2 diabetes mellitus require a distinct approach. Specific challenges to clinicians and healthcare professionals in patients with type 2 diabetes include the prevalence of peripheral and autonomic neuropathy, retinopathy, nephropathy, but also the intake of glucose-lowering medication. In addition, the psychosocial wellbeing, driving ability and/or occupational status can be affected by type 2 diabetes. As a result, the target parameters of cardiovascular rehabilitation and the characteristics of the cardiovascular rehabilitation programme in patients with type 2 diabetes often require significant reconsideration and a multidisciplinary approach. This review explains how to deal with diabetes-associated comorbidities in the intake screening of patients with type 2 diabetes entering a cardiovascular rehabilitation programme. Furthermore, we discuss diabetes-specific target parameters and characteristics of cardiovascular rehabilitation programmes for patients with type 2 diabetes in a multidisciplinary context, including the implementation of guideline-directed medical therapy.